Exchange rate policies in Asia in an era of financial globalisation: An empirical assessment. (27th February 2019) - Cavoli, Tony; Gopalan, Sasidaran; Rajan, Ramkishen S.
Abstract: Ebbs and flows of capital have complicated macroeconomic policy management for all emerging market and developing economies (EMDEs) regardless of whether they have adopted flexible or managed exchange rate regimes. In the light of the renewed interest in the trilemma versus dilemma debate, we contribute to the related literature by presenting an empirical analysis of exchange rate flexibility and intervention for selected Asian EMDEs over the time period 2001–2016. In addition to estimating augmented Frankel–Wei regressions, we employ a generalised auto‐regressive conditional heteroscedasticity (GARCH) model to assess the extent of foreign exchange (FX) intervention and whether there exist any asymmetries in the way countries intervene. Our results show that although there is greater flexibility in exchange rates, there is evidence of some countries potentially using FX intervention to manage currency movements. We also find evidence of asymmetry in intervention where exchange rate volatility responds more emphatically to FX sales than purchases.